Environmental, biological, and social factors influencing fecal adrenal steroid concentrations in female Japanese macaques (Macaca fuscata). Issue 11 (16th May 2014) - Takeshita, Rafaela S. C.; Bercovitch, Fred B.; Huffman, Michael A.; Mouri, Keiko; Garcia, Cécile; Rigaill, Lucie; Shimizu, Keiko
<x xml:space="preserve">Abstract</x> The ability to determine hormonal profiles of primate populations using non‐invasive techniques can help to monitor physical fitness, stress, and physiological responses to environmental changes. We investigated fecal glucocorticoids (fGC) and DHEAS concentrations in captive Japanese macaques (Macaca fuscata) in relation to environmental, biological, and social factors. The subjects were female Japanese monkeys from 4 months to 31 years old housed in captivity (27 in social groups and 12 in single cages). Fecal samples were collected from all females, and behavioral data from the social groups during the mating season and the following birth season. Hormonal concentrations were analyzed by enzyme immunoassay. Our results revealed that both fGC and fecal DHEAS concentrations are higher in females housed indoors in single cages than in those living outdoors in social groups. We also found that fGC concentrations were higher in the cycling females during the mating (winter) season than the lactating females in the birth (spring) season. Age was negatively associated to both fGC and fecal DHEAS levels, but the relationship between age and fecal DHEAS was more evident in females housed indoors in single cages than in females housed in outdoor social groups. We did not observe any association of dominance rank with either fecal DHEAS or fGC. This study showed that measurement of fecal DHEAS and fGC can be a good method to assess stress in Japanese macaques. These findings provide insights about the physiology of these two adrenal hormones in female Japanese macaques, which can be applied to wild populations and is fundamental for captive management and conservation biology. Am. J. Primatol. 76:1084–1093, 2014. © 2014 Wiley Periodicals, Inc.